Body Mass Index: An Effective Predictor of Ejection Fraction Improvement in Heart Failure - Ye, Li-fang; Li, Xue-ling; Wang, Shao-mei; Wang, Yun-fan; Zheng, Ya-ru; Wang, Li-hong (Frontiers in Cardiovascular Medicine, 2021)
Background: Heart failure patients with higher body mass index (BMI) exhibit better clinical outcomes. Therefore, we assessed whether the BMI can predict left ventricular ejection fraction (EF) improvement following heart failure. Methods and Results: We included 184 patients newly diagnosed with dilated cardiomyopathy and reduced EF in our center and who underwent follow-up examination of EF via echocardiography after 6 months. The EF improved at 6 months in 88 participants, who were included in the heart failure with recovered EF (HFrecEF) subgroup. Patients in whom the EF remained reduced were included in the heart failure with persistently reduced EF (persistent HFrEF) subgroup. Our analyses revealed that EF increase correlated with age (r = -0.254, P = 0.001), left ventricular diastolic dimension (LVDD; r = -0.210, P = 0.004), diabetes (P = 0.034), brain natriuretic peptide (r = -0.199, P = 0.007), and BMI grade (P = 0.000). BMI grade was significantly associated with elevated EF after adjustment for other variables (P = 0.001). On multivariate analysis, compared to patients with persistent HFrEF, those with HFrecEF had higher BMI (odds ratio [OR] = 2.342 per one standard deviation increase; P = 0.001) and lower LVDD (OR = 0.466 per one standard deviation increase; P = 0.001). ROC-curve analysis data showed that BMI > 22.66 kg/m2 (sensitivity 84.1%, specificity 59.4%, AUC 0.745, P = 0.000) indicate high probability of EF recovery in 6 months. Conclusions: Our data suggest that higher BMI is strongly correlated with the recovered EF and that BMI is an effective predictor of EF improvement in patients with heart failure and reduced EF.